Reprenstasi Ketakutan Meninggalkan Kebudayan Batak Dalam Film Ngeri-Ngeri Sedap - Oktavia Permatasari Sihombing (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
This research explores the representation of fear in the context of leaving Batak culture as depicted in the film "Ngeri-Ngeri Sedap". Through a content analysis approach, this study investigates how the fear associated with leaving cultural identity is reflected in the narrative, visuals, and characters in the film. Qualitative methods are used to analyze various film elements, including dialogue, plot, setting, and cultural symbolism. The findings indicate that the film portrays the complexity of fear experienced by individuals confronted with the conflict between tradition and modernity. These representations provide insights into the cultural dynamics within Batak society and their implications for individual identity. The study contributes to understanding how fear is associated with cultural change and how it is reflected using Roland Barthes' semiotic analysis framework. The goal of this study is to use Roland Barthes' semiotic analysis method to uncover the moral lessons that are subtly conveyed in films. The study uses qualitative descriptive methodologies and centers on specific cinema moments. While connotation is investigated to uncover the hidden meaning behind these indicators, denotation is used to identify signs as they seem on the surface. Myth analysis is another method used in this research to find concepts that are implied by the movie's plot. Through the use of Roland Barthes' semiotic approach, the study unveils "Ngeri-Ngeri Sedap"'s intricate and multilayered narrative structure. The research findings offer profound insights into the ways in which the film uses verbal and visual cues to convey moral lessons to its audience. This study enhances our knowledge of semiotic analysis in the context of film by shedding light on symbolic representations and hidden messages in audiovisual art.